Pengaruh Kinerja Keuangan Terhadap Cash Holding pada Perusahaan Sub Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2018-2020 - Rehanah Fardianti; Susi Astuti (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
This study aims to determine the effect of financial performance on cash holding. The population in this study is the banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020 as many as 45 companies. The research sample was 43 companies for 3 years so that a sample of 129 companies was obtained using purposive sampling method. Data analysis used the SPSS 25 program. The results showed that profitability (ROA) had a positive effect on cash holding, leverage (DER) had no effect on cash holding, and firm size had a negative effect on cash holding.